The Determinants of Rice Farmers’ Adoption of Sustainable Agricultural Technologies in the Mekong Delta, Vietnam - Dung, Luu Tien; Ho, Dinh Phi; Hiep, Nguyen Thi Kim; Hoi, Phan Thi (Asian Journal of Applied Economics, 2018)
Farmers’ adoption of sustainable agricultural technologies guarantees for increasing their income/profit, providing quality agricultural products for the society, and preserving tolerance limits of ecological agriculture. This study analyzes factors affecting the adoption behavior of sustainable agricultural technologies among rice farmers in the Mekong Delta, Vietnam based on the binary logit model. The result shows that factors affecting the adoption behavior are i) human capital; ii) farm size; iii) social capital; iv) extension and v) access to the market. The study also gives policy implications, which make the scientific foundation for policymakers in promoting the adoption of sustainable production.